Pemphigoid Gestationis after Spontaneous Expulsion of a Massive Complete Hydatidiform Mole - Naoki Matsumoto; Marie Osada; Kou Kaneko; Ken Ohara; Daito Noguchi; Haruhiko Udagawa; Nagazumi Suzuki; Chieko Matsumoto; Sachio Takahashi (Case Reports in Obstetrics and Gynecology)
Pemphigoid gestationis (PG) is a rare, perinatal, autoimmune, and blistering dermatosis. Only few cases of PG involving hydatidiform moles have been reported. Complete hydatidiform moles are usually evacuated by dilatation and curettage. We report a patient with a massive complete hydatidiform mole that underwent spontaneous expulsion; she subsequently developed PG. A 19-year-old unmarried nulligravid woman was referred to our hospital following excessive vaginal bleeding after an uncertain amenorrheal period. The patient presented with preshock vital signs, severe anemia, and a positive urine pregnancy test. Imaging examinations revealed a massive intrauterine mass (19 × 15 × 10 cm), suggesting a complete hydatidiform mole. She was hospitalized and treated with blood transfusion. Sixteen hours after hospitalization, the massive molar mass underwent spontaneous expulsion and bleeding ceased. Three days after the expulsion, she developed pruritic skin lesions including papules, erythemas, and bullae, which spread over her entire body. Skin biopsy revealed PG and subepidermal blister formation and linear complement C3 deposition along the basement membrane zone, and the serum anti-BP180 antibody level was found to be high on measurement. She was effectively treated with 50 mg/day of oral prednisolone. Her skin lesions disappeared, leaving pigmentation.